Wakefield excitation in nonlinear plasma by sequence of relativistic electron bunches - Maslov, V.I.; Onishchenko, I.N.; Yarovaya, I.P. (Вопросы атомной науки и техники, 2014)
The plasma wakefield excitation by long sequence of relativistic electron bunches is considered. It has been shown that taking into account ionization of the residual gas partially compensates resonance nonlinear detuning and the wakefield amplitude increases in comparison with the case of constant plasma density. Certain small excess of the plasma density on the resonant value also leads to focusing of more part of bunches, to extend the existence of the resonance and, as a result, to increase of the amplitude of the excited wakefield. Рассматривается возбуждение кильватерного поля в плазме длинной последовательностью релятивистских электронных сгустков. Показано, что учет ионизации остаточного газа частично компенсирует нелинейную расстройку резонанса, и амплитуда кильватерного поля увеличивается по сравнению со случаем постоянной плотности плазмы. Определенное малое превышение плотности плазмы над резонансным значением также приводит к фокусировке большей доли сгустков, к продлению существования резонанса и, как результат, к увеличению амплитуды возбуждаемого кильватерного поля. Розглядається збудження кільватерного поля в плазмі довгою послідовністю релятивістських електронних згустків. Показано, що врахування іонізації залишкового газу частково компенсує нелінійну розстройку резонансу, і амплітуда кільватерного поля збільшується порівняно з випадком постійної густини плазми. Певне мале перевищення густини плазми над резонансним значенням також призводить до фокусування більшої частини згустків, до продовження існування резонансу і, як результат, до збільшення амплітуди збуджуваного кільватерного поля.